For reducing premature adult mortality in India, education matters more than income - Moradhvaj Dhakad; Erich Striessnig; Nandita Saikia; Samir K.C.; Wolfgang Lutz (Proceedings of the National Academy of Sciences, 2026)
Preventing premature death is a global policy objective reflected in the SDGs. While numerous studies have found socioeconomic factors to be significantly associated with premature death everywhere in the world, the debate on the relative effect of such factors on mid-age (15 to 59 ages) has not received enough attention, particularly in low-income countries, where this question is pertinent due to scant resources in the healthcare sector. Using nationally representative, longitudinal data from the India Human Development Survey, we assess the relative importance of individual- and community-level education vs. income and wealth in India, where approximately 3 million premature deaths occur annually in mid-ages. We find a clear downward gradient in mid-age mortality with increasing education within each wealth category, whereas no consistent mortality advantage with increasing wealth status is visible within education subgroups. Multilevel logistic regression models show that the decline in the risk of death across the education spectrum by far exceeds (14% for male and 13% for female) the decline moving along the wealth distribution, even after controlling for other relevant demographic, socioeconomic, regional variables. Along with the direct effect of individual-level educational attainment, we also find a protective effect of education at the community level, particularly for women. Based on these findings, we infer that educational attainment is essential for reducing mid-age mortality in India. Population and health policies in developing countries, therefore, should focus on education to prevent adult mortality.